RADIO IN THE NEW MEDIA ECOSYSTEM: GLOBAL CHALLENGES AND LOCAL PRACTICE - Penezić, Slobodan M; Selenić, Uroš (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
The text aims to present the current state and changes in the functioning of radio media organizations (RMOs), while simultaneously summarizing their basic characteristics and contemporary operating models, with a primary focus on new technical-technological (TT) conditions that, like other media actors, predominantly direct them toward the paths of necessary transformation. Along with an overview of the specifics of this part of the media industry, its comparative advantages, and the adaptation process to the new TT environment, global trends in this regard and the situation within the domestic media system (in Serbia) are also described. Concurrently, new radio operating models are presented and analyzed, taking into account primarily the new TT framework of work, new audience habits, and the new way RMOs operate, while also presenting the key features of the local radio market. In this way, the goal is to examine the paths of transforming traditional radio into a modern radio metamedium of the 21st century, following the main thesis that success in this regard and the market sustainability of RMOs depend on their relationship with the new TT conditions and the use of inherent radio comparative advantages, while also adhering to responsible editorial policies and high-quality content. The objective is, therefore, a collection of diagnoses and recommendations presented in the concluding segment of the text, which can today be reasonably addressed to all media and other relevant actors who have an impact on the further development of radio media. This is reflected in three dimensions of their functioning in the 21st century: organizational, user, and the dimension of challenges within the local media environment.
Keywords: radio; radio stations; radio media organizations; radio transformation; convergence; media complex; media system; metamedium